Aplikasi Crowdsource Pencarian Jasa Fotografer Videografer Berbasis Android - Sanjaya, Cenius; Rostianingsih, Silvia; Andjarwirawan, Justinus (Jurnal Infra, 2018)
As technology grows and becomes more sophisticated, the impact will make it easier for humans to search for anything they want. Searching for services in photography and videography fields is still essential. From people's perspective in searching of services, the minimum information about quality of service providers makes clients hesitate to use the service. From the provider's perspective the problem is the offered price from service searchers doesn't fit the provider's criteria and the slow payment system makes the provider feel disadvantageous.To solve the problem, an android based application is made. This application has features such as record, rating and review where it helps the provider to show the quality of the jobs that have been done. Also it has portfolio features with auto watermark that supports the quality of the service provider so it won't be claimed by any irresponsible party. Then the bid feature also helps service searcher to get the best price which matches the maximum budget they have and enables the service providers to freely offer their best price for the searchers. Payment system in this application uses third party where the user will pay to application and if it's finished the admin will transfer it to the service provider.After getting through the testing phase, the application can help the searcher to look for service provider with the best price and quality that's trusted and well-known. This app as a whole is scored 84% from respondents.